Pengembangan E-Modul Pemeliharaan Mesin Kendaraan Ringan untuk Siswa Kelas XI TKRO di SMKN 2 Lamongan - Rudy Prasetya Hutama; Nurmida Catherine Sitompul; Hartono Hartono (IKIP PGRI Bojonegoro, 2022)
Abstract: The aims of this study were: (1) to produce an e-module for light vehicle engine maintenance in class XI TKRO SMKN 2 Lamongan., and (2) determine the feasibility of an e-module for light vehicle engine maintenance in class XI TKRO SMKN 2 Lamongan. This development research follows the stages of developing the ADDIE model which consists of analysis, design, development, implementation, and evaluation. Data collection was carried out through an e-module product assessment questionnaire sheet, and student and teacher response questionnaire sheets. The research data were analyzed by quantitative descriptive. This study resulted in: (1) an e-module which was developed using the Flip PDF pro software. The end result is an electronic book that can be accessed anywhere as long as internet access is available. (2) The assessment from the material expert was obtained that the e-module was categorized as feasible with an assessment percentage of 85%, from the design expert it was categorized as feasible with a percentage of 89%, from the media expert the percentage of assessment was 87% in the appropriate category, from users, namely colleagues, it was obtained the percentage of assessment is 91% with a very decent category from the responses of small group students, namely 8 students, the results are in a very decent category with a percentage of 92% and a large group of 30 students obtained very decent results with a percentage of 93%. Keywords: E-Module, Light Vehicle Engine Maintenance, Research Development, teaching materials Abstrak: Tujuan dari penelitian ini adalah: (1) Menghasilkan e-modul pemeliharaan mesin kendaraan ringan pada siswa kelas XI TKRO SMKN 2 Lamongan., dan (2) mengetahui kelayakan e-modul pemeliharaan mesin kendaraan ringan pada siswa kelas XI TKRO SMKN 2 Lamongan. Penelitian pengembangan ini mengikuti tahap-tahap pengembangan model ADDIE yang terdiri dari analisis (analysis), desain (design), pengembangan (development), implementasi (implementation), dan evaluasi (evaluation). Pengumpulan data dilaksanakan melalui lembar angket penilaian produk e-modul, dan lembar angket respon siswa dan guru. Data penelitian dianalisis dengan deskriptif kuantitatif. Penelitian ini menghasilkan: (1) e-modul yang dikembangkan menggunakan softwere flip pdf pro yang hasil akhirnya adalah buku elektronik yang bisa diakses dimana saja selama tersedia akses internet. (2) Penilaian dari ahli materi diperoleh bahwa e-modul dikategorikan layak dengan persentase penilaian sebesar 85%, dari ahli desain dikategorikan layak dengan prosentase 89%, dari ahli media diperoleh persentase penilaian sebesar 87% dengan kategori layak, dari pengguna yaitu rekan sejawat diperoleh persentase penilaian sebesar 91% dengan kategori sangat layak dari respon siswa kelompok kecil yaitu 8 siswa diperoleh hasil dengan kategori sangat layak dengan persentase sebesar 92% dan kelompok besar yaitu 30 siswa diperoleh hasil sangat layak dengan prosentase sebesar 93%. Kata Kunci: e-modul, Pemeliharaan Mesin Kendaraan Ringan, Penelitian Pengembangan, bahan ajar.